Symmetries and conservation laws of certain classes of complex partial diﬀerential equations - Phidane, Thilivhali (My University, 2018)
Lie symmetry analysis is an established method for generating symmetries of diﬀerential equations. We apply this method together with fundamental theorem of double reduction. In particular, Noether symmetries and some associated conservation laws are constructed in our investigation to ﬁnd exact solutions of higher order partial diﬀerential equations and complex partial diﬀerential equations.
A dissertation submitted to the Faculty of Science, University of Witwatersrand, in fulﬁllment of the requirements for degree of Master of Science June 4, 2018
Keywords: Symmetric functions; Differential equations; Mathematical physics